Social cognition and mood: relationships between depression, self-esteem, and evaluations of other people : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in psychology, Massey University - Conway, Les (Massey University, 1990)
This study examined the relationships between depression, self-esteem, and evaluations of other people. Three major hypotheses were addressed. The first hypothesis involves the extent to which people with low self ratings give low ratings to others. Secondly, the hypothesis that depressed men perceive women as more competent and powerful than men is investigated. Thirdly, the hypothesis that self-esteem mediates the relation between depression and social cognition is explored. Additional issues addressed were first, whether the evaluations of other people made by depressed subjects differ as a function of the sex of others and secondly, whether there is utility in differentiating components of self-esteem in studies of depression and social cognition. 262 non-student subjects, aged 16 to 'over 60' years responded to a questionnaire incorporating three forms (self, female others, and male others) of an evaluation rating scale. Limited support was obtained for the first two hypotheses. Mediator variable analysis refutes the hypothesis of a strong mediating effect of either self-acceptance or social confidence in the relationship between social cognition and depression. Implications of these findings for social comparison processes, studies of stereotypic biases, and further research on depression are discussed.
Keywords: Social perception; Social psychology; Self-esteem